Analisis Kajian Semantik Kalimat Verbal (Jumlah Fi’liyah) dari Segi Penggunaannya dalam Pembelajaran - Nara Soma; Asrina Asrina (Murabby: Jurnal Pendidikan Islam, 2024)
The purpose of this study is to describe the semantic study of verbal sentences (number of fi’liyah) in terms of their use in communicating. In the learning of language, verbal sentences have a very important role in the achievement and success of an Arabic language learner. Because verbal words discuss the role of words and subjects in the language itself. As to the purpose of this research is sought to be able to answer about the use of Arabic verb sentences in sentences and against its use in communicating. This research includes qualitative research with a library study approach, carried out using the literature ( library) of the previous research, where the researchers do not dive into the field in carrying out research because it can be done in the library or other places as long as there are sources of reading suitable for discussion such as journals, dictionaries, documents, magazines, etc. It was found that the verbs were divided into five types: the positive (mutsbat), the interrogative (istifham), the commanded (amarg), the denial (nafi), and the prohibition (prohibition). (kalam nahi).